Identifikasi struktur bawah permukaan tanah menggunakan metode geolistrik konfigurasi Wenner-Schlumberger di Kabupaten Rokan Hulu - Lihayati, Rifa; Septania, Nadia Luanda; Haroky, Faruq (JURNAL PENDIDIKAN DAN SAINS, 2024)
This study aims to determine the subsurface structure using the geoelectric configuration method Wenner-Schlumberger in the geothermal area of Pawan Village. Data retrieval were carried out in 4 paths with different lengths of each track. Line 1 is located at 00°49'31.49" N and 100°15'23.87" E indicating that the hot spring water source area has subsurface structures in the form of groundwater, clay, silty clay, sandstone, alluvium and sand, limestone. Line 2 is located at the coordinates 00°49'34.82" N and 100°15'32.04" E shows the subsurface structure in the form of ground water, clay, silt clay, sand silt, limestone, sandstone and slate. Line 3 is located at the coordinates 00°49'34.34" N and 100°15'28.56" E shows the subsurface structure of groundwater, clay, silt, sandy silt / brick, gravel, stone write, and sandstone. Line 4 is located at 00°49'33.06" N and 100°15'25.69" E shows the subsurface structure in the form of magnetites, groundwater, silt clay, conglomerates, sandstone, and basal. The distribution of hot water is estimated to flow through the surface and much accumulates in the soil layer in the form of sandstone.